(untitled) (Journal of Tourism & Adventure, 2018)
Natural disasters have a catastrophic impact on the lives of humans, interrupting their social and economic activities to a great extent. Communities that are located in high-risk regions encounter greater challenges in developing a resilient and sustainable tourism economy (Tsai et. al., 2016). The past examples of tsunamis, earthquakes, volcanic eruptions all over the world have shown that there are two sides of the issue in terms of tourism sector. First, the devastating effects of the natural disaster slow down the tourism sector like all other activities in a particular destination. On the other hand, the natural disasters are capable of fostering the strong feelings of solidarity (Goodwin, 2005), luring the global interest to the region for further economic opportunities, including tourism. The aim of this manuscript is to investigate the influence of drawbacks and possible positive impacts of natural disasters on tourism activities and to model them in a proper manner. The paper will start with a body of literature on the impact of natural disasters on the tourism industry based on the previous studies. The study will be dealing with the question how natural disasters have an impact on tourism through economic aspects, destination image and the degree of community activity. The methodology will be literature review and critical evaluation of the findings. Finally, a model will be suggested in order to provide a quantitative analysis for the natural disasters, including the possible related economic and social variables.